Fast reconstruction of Raman spectra from narrow-band measurements based on Wiener estimation - Chen, Shuo (2013)
Raman spectroscopy has demonstrated great potential in the study of biological molecules in a variety of biomedical applications. But slow data acquisition due to weak Raman signals from these molecules has prevented its wide use especially in an imaging setup. We propose a novel method to reconstruct the entire Raman spectrum from a few narrow-band measurements based on Wiener estimation. This method has been tested on Raman spectra from individual cells and shown fast speed and excellent accuracy. This method represents a new direction to speed up Raman data acquisition in an imaging setup to investigate fast changing phenomena.